2002
DOI: 10.1007/s00277-002-0480-5
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate doses of melphalan and dexamethasone are better than vincristine, adriamycin, and dexamethasone (VAD) and polychemotherapy for the treatment of primary plasma cell leukemia

Abstract: Primary plasma cell leukemia (PPCL) is a rare form of disease accounting for 1-2 percent of myelomas. Between September 1990 and November 2000, among 540 patients with myeloma studied, 24 fulfilled the criteria of PPCL (4.4 percent). We found high frequencies of female patients (62 percent), Bence Jones proteinuria (79 percent), anemia (88 percent), bleeding (54 percent), confusional syndrome (42 percent), weight loss (71 percent), hepatomegaly (25 percent), splenomegaly (21 percent), leukocytosis (62 percent)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 5 publications
4
6
0
Order By: Relevance
“…The clinical features of PCL are similar to those of MM, with the addition of extensive involvement of visceral organs, fewer bone lesions, and higher frequency of anemia and thrombocytopenia [5]. In our study, the lower platelet count in patients with PCL is concordant with previous reports [1, 2,5,6,7], and a higher bone marrow cellularity in patients with primary PCL than in patients with MM is observed.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The clinical features of PCL are similar to those of MM, with the addition of extensive involvement of visceral organs, fewer bone lesions, and higher frequency of anemia and thrombocytopenia [5]. In our study, the lower platelet count in patients with PCL is concordant with previous reports [1, 2,5,6,7], and a higher bone marrow cellularity in patients with primary PCL than in patients with MM is observed.…”
Section: Discussionsupporting
confidence: 82%
“…The clinical features of PCL are similar to those of MM, with the addition of extensive involvement of visceral organs, fewer bone lesions, and higher frequency of anemia and thrombocytopenia [5]. In our study, the lower platelet count in patients with PCL is concordant with previous reports [1, 2,5,6,7], and a higher bone marrow cellularity in patients with primary PCL than in patients with MM is observed. Primary PCL has a more aggressive clinical presentation than MM, with a higher frequency of extramedullary involvement, anemia, thrombocytopenia, hypercalcemia, renal failure, increased lactate dehydrogenase and β 2 -microglobulin [1, 2,5,6,7].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In the past 30 years, several clinical studies [4,5,6,7,8] with more than 20 PCL patients have been reported and the characteristic of PCL patients in the Western countries began to be understood. Patients with this entity usually have a fulminant course and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%